Pemindahan Supply Point Penjualan Hsfo Menggunakan Metode F-AHP pada PT Pertamina Patra Niaga Jawa Timur - Zia Urrahman, Muhammad; Machsus, Machsus (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the best location for relocating PT Pertamina Patra Niaga's High Sulfur Fuel Oil (HSFO) Supply Point in East Java to improve distribution efficiency and reduce logistics costs. The research method used is the Fuzzy Analytical Hierarchy Process (F-AHP) approach, which combines quantitative and qualitative analysis through expert interviews and focus group discussions (FGDs) to assign weights to factors and subfactors influencing location selection. The results indicate that location accessibility has the highest weighting of 0.614, surpassing financial factors at 0.386. The market location subfactor is the top priority, with a weighting of 0.420, as proximity to HSFO consumption centers provides significant distribution efficiency. Based on the F-AHP analysis, TBBM Tuban was selected as the most optimal location with a score of 0.567, surpassing Camplong Madura, Malang, and Madiun. The study concludes that relocating the Supply Point to Tuban is a strategic move that can increase cost efficiency by up to 25%, accelerate distribution, and strengthen the company's competitiveness and operational sustainability.   Keywords: HSFO, Location Selection, Fuzzy AHP, Accessibility, Distribution Efficiency